Law No. 77 of the year 2017 On Granting A Special Raise To The State Civil Servants Who Are Not Addressed with the Civil Service Law Law No. 78 of the year 2017 On Granting An Exceptional Cost-of-living Allowance to the State Civil Servants Who Are Not Addressed with the Civil Service Law Law No. 79 of the year 2017 On Determining the Minimum Limit of the Periodic Raise Prescribed by the Civil Service Law No. 81 of the Year 2016, and Granting An Exceptional Cost-of-living Allowance to the State Civil Servants Addressed with the Provisions Therefore = القانون رقم 77 لسنة 2017 بشأن منح زيادة خاصة لموظفي الدولة المدنيين غير المعالجين مع قانون الخدمة المدنية رقم 78 لسنة 2017 بشأن منح بدل استثنائي لتكاليف المعيشة لموظفي الدولة غير المعالجين مع قانون الخدمة المدنية ومنح بدل استثنائي لتكاليف المعيشة لموظفي الخدمة المدنية في الدولة الذين يجري تناولهم مع الأحكام. - Egypt; The middle east library for economic services, translator. (2025)
Law No. 77 of the year 2017 On Granting A Special Raise To The State Civil Servants Who Are Not Addressed with the Civil Service Law -- Law No. 78 of the year 2017 On Granting An Exceptional Cost-of-living Allowance to the State Civil Servants Who Are Not Addressed with the Civil Service Law -- Law No. 79 of the year 2017 On Determining the Minimum Limit of the Periodic Raise Prescribed by the Civil Service Law No. 81 of the Year 2016, and Granting An Exceptional Cost-of-living Allowance to the State Civil Servants Addressed with the Provisions Therefore قانون رقم 77 لسنة 2017 بمنح علاوة خاصة للعاملين بالدولة من غير المخاطبين بقانون الخدمة المدنية -- رقم 78 لسنة 2017 بمنح علاوة غلاء استثنائية للعاملين بالدولة من غير المخاطبين بقانون الخدمة المدنية -- قانون رقم 79 لسنة 2017 بتحديد الحد الأدنى للعلاوة الدورية المقررة بقانون الخدمة المدنية الصادر بالقانون رقم 81 لسنة 2016 وبمنح علاوة غلاء استثنائية للمخاطبين بأحكامه